2020
DOI: 10.1103/physrevb.102.035429
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature insulating phase of the Si(111)7×7 surface

Abstract: We investigated the electronic structure of the Si(111)-7×7 surface below 20 K by scanning tunneling and photoemission spectroscopies and by density functional theory calculations. Previous experimental studies have questioned the ground state of this surface, which is expected to be metallic in a band picture because of the odd number of electrons per unit cell. Our differential conductance spectra instead show the opening of an energy gap at the Fermi level and a significant temperature dependence of the ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(86 citation statements)
references
References 70 publications
(127 reference statements)
6
79
1
Order By: Relevance
“…After this paper was accepted, new experimental and theoretical results by Modesti et al [ 57 ] appeared showing that “experimental observations point to an insulating ground state and contradict the prediction of a metallic surface obtained by density functional theory” (for the DAS model). They attribute this to a possible degenerate magnetic state and/or the failure of mean field theory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After this paper was accepted, new experimental and theoretical results by Modesti et al [ 57 ] appeared showing that “experimental observations point to an insulating ground state and contradict the prediction of a metallic surface obtained by density functional theory” (for the DAS model). They attribute this to a possible degenerate magnetic state and/or the failure of mean field theory.…”
Section: Resultsmentioning
confidence: 99%
“…Several reasons for the disparity between their experimental and theoretical results for the 7 × 7 are also discussed. [ 57 ]…”
Section: Discussionmentioning
confidence: 99%
“…For the 7 × 7, this boils down to performing high precision calculations that look for small energy differences (≈10s of meV) to delineate structures. [ 13 ] As shown here, this contrasts GW calculations of Si which minimize self‐interaction energy errors [ 33 ] and typically reduce electron energies by ≈0.3 eV per state atom −1 for dozens of surface atoms and their electrons. This stronger bonding of certain electrons does not enter into mean field DFT calculations and can skew the total electron bonding and favor different structure and interactions.…”
Section: Examination Of Experimental and Theoretical Resultsmentioning
confidence: 81%
“…Figure 4b shows the total minority and majority PDOS of two distinct types of AA from a recent study that examined them with high resolution. [ 13 ] This calculation uses denser k‐pt sampling and a 10 meV Fermi broadening, but only over a limited energy range of 0.5 eV about E F , [ 13 ] as indicated by the energy range brackets. Here, the AAs are grouped into two sets on each side of the unit cell: those in the corner of the unit cell, co‐AAs, and those on the side, s‐AAs.…”
Section: Examination Of Experimental and Theoretical Resultsmentioning
confidence: 99%
“…Very recently, spin polarized calculations suggested that the electronic structure of the DAS structure is not as simple as once believed, and called for a re-examination of the electronic structure of the 7 Â 7. 64 Hence, the structure of the 7 Â 7 becomes even more important in understanding these unusual properties of the Si(111) surface.…”
Section: Introductionmentioning
confidence: 99%